2008
DOI: 10.1007/s11185-007-9020-1
|View full text |Cite
|
Sign up to set email alerts
|

Russian in post-Soviet countries

Abstract: Аннотация В статье проводится сравнительный анализ языковой политики в отно-шении русского языка и языковой практики на территории четырнадцати пост-советских стран. Вначале анализируется взаимосвязь между языковой политикой, которая предопределяет статус русского языка в каждой из стран, языковой си-туацией в общественной сфере, в том числе в области образования и трудоустрой-ства, и языковой ситуацией в частной практике, которая позволяет понять настоя-щее положение русского языка и предсказать тенденции его… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 29 publications
0
35
0
3
Order By: Relevance
“…For example, Georgia's former president Mikhail Saakashvili known for his anti‐Russian agenda argued: ‘To have a career, you don't need to know Russian. You need to study English, Turkish’ (Pavlenko, , p. 70). On the other hand, in defence of a recent government initiative to reopen some foreign language schools in Armenia, the education minister Armen Ashotian suggested that the knowledge of Russian is simply a matter of Armenians remaining ‘competitive’ in today's marketplace (Grigoryan, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Georgia's former president Mikhail Saakashvili known for his anti‐Russian agenda argued: ‘To have a career, you don't need to know Russian. You need to study English, Turkish’ (Pavlenko, , p. 70). On the other hand, in defence of a recent government initiative to reopen some foreign language schools in Armenia, the education minister Armen Ashotian suggested that the knowledge of Russian is simply a matter of Armenians remaining ‘competitive’ in today's marketplace (Grigoryan, ).…”
Section: Introductionmentioning
confidence: 99%
“…According to different estimations, there are between 2,000, 400 hundred and 3,000,000 people (2.9%-3.7% of the population) living in Germany who consider Russian to be their first language (Polian 2005;Brehmer 2007). This is a heterogeneous migrant group, including ethnic Germans, Jews and their family members, Russian spouses of German citizens, scientists, students and asylum-seekers from different countries of the former Soviet Union, where Russian is still widespread as a common language (e.g., Pavlenko 2008). The biggest group of Russian-speaking immigrants in Germany are ethnic Germans, who received the right to immigrate to Germany due to the Late Repatriates Law.…”
Section: Russian-speaking Immigrants In Germany and Israelmentioning
confidence: 99%
“…To date, several comprehensive studies on the language situation are available (Baskakov 1992;Fireman 2006;Pavlenko 2008aPavlenko , 2008bSmagulova 2008). To date, several comprehensive studies on the language situation are available (Baskakov 1992;Fireman 2006;Pavlenko 2008aPavlenko , 2008bSmagulova 2008).…”
Section: Kazakhstanmentioning
confidence: 99%
“…In Ukraine, due to the close relatedness of the varieties and exposure to Ukrainian, many Russian-speakers had at least a passive command of Ukrainian (Bilaniuk and Melnyk 2008: 345, 346-347;Vakhtin et al 2003). Now the situation has changed in the terms of language policy and language status (on various versions of de-Russification in the post-Soviet countries see Pavlenko [2008aPavlenko [ , 2008b) but the question remains: what has changed in the linguistic behavior and repertoire of individual speakers? Now the situation has changed in the terms of language policy and language status (on various versions of de-Russification in the post-Soviet countries see Pavlenko [2008aPavlenko [ , 2008b) but the question remains: what has changed in the linguistic behavior and repertoire of individual speakers?…”
Section: Introductionmentioning
confidence: 99%